Spójność i konkurencyjność regionów w Polsce w latach 2000-2002 - Markowska-Przybyła, Urszula (The cohesion and competitiveness of regions in Poland in 2000-2002, 2006)
The Aspiration for higher socio-economic cohesion became a natural aim of economic policy in in Poland EU as well as. This and the processes of polarization, caused to a large extent by globalization were considered natural. The aim of the paper is the analysis of economic and social cohesion and competitiveness of Polish regions in inter- and intraregional dimension as well as showing tendency between 2000 and 2002. The paper focuses on two elements of the analysis: reconnoiter of actual state and interpretation of it. The most difficult and demanding further, in-depth analysis is the third element of the analysis - drawing conclusions. The main conclusion resulting from the analysis is the following - the theses about increase of inter- and intraregional polarization, about space’s metropolisation and the formation of archipelagos of development haven’t been confirmed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 134-151